x2 − 12x + 27?
Answer:
The factors of the expression in the question x² − 12x + 27 = 0 are (x - 9)(x -3) .
Step-by-step explanation:
As given the expression in the question be as follow .
x² − 12x + 27 = 0
x² - 9x - 3x + 27 = 0
x (x - 9) -3 (x -9) = 0
(x - 9)(x -3) = 0
Therefore the factors of the expression in the question x² − 12x + 27 = 0 are (x - 9)(x -3) .
The factored form of the polynomial ( x² - 12x + 27 ) is ( x-3 )( x-9 ).
Given that;
First, we think of two numbers where their addition gives -12 and their multiplication gives 27.
-3 and -9 fits perfectly.
Hence we have;
x² - 12x + 27
( x-3 )( x-9 )
Therefore, the factored form of the polynomial ( x² - 12x + 27 ) is ( x-3 )( x-9 ).
Learn more about factorizations here: brainly.com/question/1863222
#SPJ5
B. x-3y=-3
C. 3x+y=-6
D. 6x+2y=2 Two lines are parallel. The equation for the first line is y=-3x+5. Which of the following can't be the equation of the second line?
A. y=-3x+2
B. x-3y=-3
C. 3x+y=-6
D. 6x+2y=2 @Mathematics
The solutions of the equation in the interval are and
Further explanation:
Given:
The function is
The first derivative is zero.
Explanation:
The given function is
Differentiate the function with respect to .
Substitute for
In the interval the x-coordinates are
The solutions of the equation in the interval are and
Learn more:
Answer details:
Grade: High School
Subject: Mathematics
Chapter: Application of derivatives
Keywords: derivative, x – coordinates, interval, far, 2x, sin2x, coordinates, 0, 2pi, y-coordinate.